2005
DOI: 10.1128/jb.187.12.4033-4041.2005
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Pseudomonas putida KT2440 Gene Expression in the Maize Rhizosphere: In Vitro Expression Technology Capture and Identification of Root-Activated Promoters

Abstract: Pseudomonas putida KT2440, a paradigm organism in biodegradation and a good competitive colonizer of the maize rhizosphere, was the subject of studies undertaken to establish the genetic determinants important for its rhizospheric lifestyle. By using in vivo expression technology (IVET) to positively select single cell survival, we identified 28 rap genes (root-activated promoters) preferentially expressed in the maize rhizosphere. The IVET system had two components: a mutant affected in aspartate-␤-semialdehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(68 citation statements)
references
References 50 publications
4
64
0
Order By: Relevance
“…Lugtenberg and Dekkers (21) have shown that utilization of organic acids by P. fluorescens is the nutritional basis governing the ability of this organism to colonize tomato roots. Genes in pseudomonads encoding proteins with functions in nutrient acquisition and in energy generation are up-regulated in the rhizosphere or when bacteria were exposed to the soil environment as revealed by in vivo expression technology-based approaches (22,23). Differences in expression of these genes in response to the var.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lugtenberg and Dekkers (21) have shown that utilization of organic acids by P. fluorescens is the nutritional basis governing the ability of this organism to colonize tomato roots. Genes in pseudomonads encoding proteins with functions in nutrient acquisition and in energy generation are up-regulated in the rhizosphere or when bacteria were exposed to the soil environment as revealed by in vivo expression technology-based approaches (22,23). Differences in expression of these genes in response to the var.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo expression technology is now established as a method of analyzing bacterial gene expression in the rhizosphere as an approach for the identification of genes involved in microbe-plant interactions (22,23,29,35). One clear advantage of in vivo expression technology is that investigations are carried out in the appropriate environment in the organism of interest; there is no extrapolation from in vitro model systems.…”
Section: Evaluation and Comparison With Other Techniques To Study Rhizo-mentioning
confidence: 99%
“…Genes involved in root exudate usage, root attachment, and survival are induced in bacteria colonizing roots (120,121). In vitro expression technology (IVET) (122), proteomic analysis, microarray and RNA Seq transcriptomics, and genetic analysis have revealed rhizobial (120,121,123), Pseudomonas (124,125), Streptomyces (126), and other bacterial genes expressed on roots or rhizospheres. Similarly, bacteria may differentially express genes when in guts.…”
Section: Similar Bacterium-host Interactions In Guts and Rootsmentioning
confidence: 99%
“…A publication by Ramos-González et al (37) showed that it can also be true for P. putida, as the promoter of colRS was activated in the maize rhizosphere. In a recent paper, we demonstrated that the P. putida two-component system ColRS is necessary for the accumulation of phenol-utilizing (Phe ϩ ) mutants, which arise due to transposition of Tn4652 (18).…”
mentioning
confidence: 99%